Dampak Pembangunan Wisata Sport Tourism Pertamina Mandalika International Circuit Dalam Aspek Ekonomi - Ayu Rahmatika, Baiq Della (Politeknik Pariwisata Medan, 2024)
This research analyzes the economic impact of the construction of the Pertamina Mandalika International Circuit in Lombok, West Nusa Tenggara, as a sport tourism destination in Indonesia. This circuit aims to attract international events such as MotoGP and the World Superbike Championship, as well as contribute to the development of the Mandalika Special Economic Zone (KEK). Using descriptive qualitative methodology, data was collected from various secondary sources. The research results show that this circuit makes a significant contribution to the local economy, such as increasing tourism income, MSME transactions and job creation. For example, the 2023 MotoGP event increased the local economy by 3.5% and created transactions of around IDR 4.5 trillion. In addition, there is an indirect economic impact on the transportation sector. However, this development has also faced criticism regarding its environmental impact and dependence on international events. It is recommended that development be carried out in a sustainable manner, involving local communities to maximize economic and social benefits while maintaining environmental balance.